2009
DOI: 10.1128/mcb.00847-09
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Responsive Transcription Factor 1 (MTF-1) Activity Is Regulated by a Nonconventional Nuclear Localization Signal and a Metal-Responsive Transactivation Domain

Abstract: Metal-responsive transcription factor 1 (MTF-1) mediates both basal and heavy metal-induced transcription of metallothionein genes and also regulates other genes involved in the cell stress response and in metal homeostasis. In resting cells, MTF-1 localizes to both the cytoplasm and the nucleus but quantitatively accumulates in the nucleus upon metal load and under other stress conditions. Here we show that within the DNA-binding domain, a region spanning zinc fingers 1 to 3 (amino acids [aa] 137 to 228 in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
(62 reference statements)
3
34
0
Order By: Relevance
“…Do these findings mean that metal inducibility is coupled to nuclear export function, such that MTF-1 must shuttle between nucleus and cytoplasm? This scenario is likely an oversimplification, as our previous work has shown that upon inhibition of nuclear export by the drug LMB, human MTF-1 is confined to the nucleus but still retains a large part -though not all -of its metal inducibility (Lindert et al, 2009). One also has to keep in mind that the NES motif overlaps with the acidic activation domain, thus a change in one might affect the other.…”
Section: A B C D E Fmentioning
confidence: 99%
See 4 more Smart Citations
“…Do these findings mean that metal inducibility is coupled to nuclear export function, such that MTF-1 must shuttle between nucleus and cytoplasm? This scenario is likely an oversimplification, as our previous work has shown that upon inhibition of nuclear export by the drug LMB, human MTF-1 is confined to the nucleus but still retains a large part -though not all -of its metal inducibility (Lindert et al, 2009). One also has to keep in mind that the NES motif overlaps with the acidic activation domain, thus a change in one might affect the other.…”
Section: A B C D E Fmentioning
confidence: 99%
“…In MTF-1, the zinc fingers are involved in metal response (Bittel et al, 1998;Zhang et al, 2003) and in humans (and presumably in Anguis) -but not in rodents -the acidic activation domain can independently respond to metals (Lindert et al, 2009). Because the difference in metal response between human and mouse MTF-1 has been mapped to the nuclear export signal/ acidic activation domain (Lindert et al, 2009), we compared the activity of the NES motif of Anguis with that of its human and mouse counterparts and with selected point mutants. As shown in Figure 4, the NES domains Figure 4 In contrast to mouse MTF-1, reptile and human MTF-1 harbor a strong nuclear export (NES) function.…”
Section: Brought To You By | Mit Librariesmentioning
confidence: 99%
See 3 more Smart Citations